Assessing the Efficiency Level of Separation Centers Dormitories related to the separation center for students with addicted parents that lack competency to take care of their children - Molouk Khadem Ashkezari (Drug Control Headquarters, Research and Education Office, 2003)
Addiction to drugs is one of the social problems the negative consequences of which are not merely limited to the addicted person. On the other hand, such negative consequences will also overshadow the person's family and society and inflicts irreparable damage on them. Such consequences may in some cases lead to the perpetration of crimes such as child abuse in the family. In this way the family will no longer remain as a safe place for the child and the child will start doing misdeeds, become addicted and end up as a person who suffers from behavioral abnormalities. The setting up of separation dorms is within the framework of taking into account the problems related to these children. The current research has made an assessment of the efficiency of the said centers after the launching of their activities. The basic goal pursued by the research is to see whether the goals set for the separation plan have been materialized and to see whether those participating in the plan were admitted or discharged based on relevant sets of rules. There is full supervision over the implementation of the plan and the second part goes to surveying the level of individuals' satisfaction over the plan. Moreover, the level of contribution by membering organizations in the implemen- tation of the plan and the rate of its success and solutions for the improvement of the plan were taken into account. The method of research applied is based on documented evidence and surveys. The collection of data in this research was carried out through indexing, filling questionnaires, interviews as well as direct As far as the mental health of abusers is concerned, 12.5 percent of abusers were healthy and 87.5 percent were suspicious of mental disorder. Moreover, a meaningful relationship was observed between drug abuse in prison and disorders, physical pains, obsession, depression and psychosis. Based on the results, opium was the major drug used in prisons. High-risk behaviors were also observed among prison inmates.